Povezanost partnerske navezanosti staršev z njihovimi vzgojnimi stili - Jurič, Sabina (Psihološka obzorja (Ljubljana), 2009)
The child-mother relation in infancy was found very important not only as a predictor of a child's social adaptation, personality predisposition and capacity development, but also as a prototype of establishing contacts with others later in life (Bowlby, 1975). These early attachment bondings with the child's mother are the basis for all close relationships with potential partners later in life. The survey covers the attachment factors of two parents (30 to 60 years old) and their style of parenting their 14- to 15-years-old adolescent. The participants were the primary school pupils of Gorenjska and Ljubljana regions. Adult attachment style was measured with Experience in Close Relationship Questionnaire - Revised (Fraley, Waller in Brennan, 2000). The children completed 30-item Parental Authority Questionnaire for the Mother's and Father's Parenting Style (Buri, 1991). We expected that the parents with low results in Anxiety and Avoidance were the ones who mostly used the authoritative parenting style compared to the parents with higher results of Anxiety and Avoidance in their relationship. The second hypothesis was that high results in Anxiety in parental relationship would mean a more authoritarian parenting style. The results confirmed our assumptions. Parents with a secure mutual relationship mainly raised their children in an authoritative manner with lots of warmth, support and appropriate borders. The second hypothesis was confirmed for fathers only. Fathers with high Anxiety in partner relationship (fear of abandonment, feelings of uncompetency) mostly raised their children in an authoritarian manner. The authoritarian manner consists of many strict borders, a lot of control and obedience. The connection of Anxiety in partnership and authoritarian parenting style was not significant for mothers.
Keywords: navezanost; attachment theory; partnerski odnosi; vzgojni stili; družinski odnosi; psihologija; psychology